Effects of Exercise on DNA Methylation: A Systematic Review of Randomized Controlled Trials - Etayo-Urtasun, Paula; Sáez de Asteasu, Mikel L.; Izquierdo, Mikel (Sports medicine (Auckland), 2024)
Background Regular exercise reduces chronic disease risk and extends a healthy lifespan, but the underlying molecular mechanisms remain unclear. DNA methylation is implicated in this process, potentially altering gene expression without changing DNA sequence. However, previous findings appear partly contradictory. Objective This review aimed to elucidate exercise effects on DNA methylation patterns. Methods PubMed, Scopus and Web of Science databases were searched following PRISMA 2020 guidelines. All articles published up to November 2023 were considered for inclusion and assessed for eligibility using the PICOS (Population, Intervention, Comparison, Outcomes and Study) framework. Randomized controlled trials that assessed the impact of exercise interventions on DNA methylation in previously inactive adults were included. We evaluated the methodological quality of trials using the PEDro scale. Results A total of 852 results were identified, of which 12 articles met the inclusion criteria. A total of 827 subjects were included in the studies. Intervention lengths varied from 6 weeks to 12 months. Most trials indicated that exercise interventions can significantly alter the DNA methylation of specific genes and global DNA methylation patterns. Conclusions The heterogeneity of results may arise from differences in participant demographics, intervention factors, measurement techniques, and the genomic contexts examined. Future research should analyze the influences of activity type, intensity, and duration, as well as the physical fitness outcomes on DNA methylation. Characterizing such dose–response relationships and identifying genes responsive to exercise are crucial for understanding the molecular mechanisms of exercise, unlocking its full potential for disease prevention and treatment.